Pengaruh Kelengkapan Produk Terhadap Keputusan Pembelian Konsumen Pada Toko Retail Mutiara Jaya - Ikhsan, Wandi Nur; Junianto, Eko (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study was conducted at the Mutiara Jaya Pekanbaru Retail Store, the respondents of this study were 96 people, rounded up to 100 respondents, where the sample of this study was customers of the Mutiara Jaya Pekanbaru Retail Store. The purpose of this study was to determine the Effect of Product Completeness on Consumer Purchasing Decisions at the Mutiara Jaya Retail Store with the results of the hypothesis test showing that t count (4.854) t table (1.98447) with sig 0.000 sig 0.05, so it can be concluded that in this study there is a significant influence on Product Completeness on Consumer Purchasing Decisions at the Mutiara Jaya Retail Store. And the influence of the Product Completeness variable on Consumer Purchasing Decisions can be seen from the coefficient of determination (R2) value of 19.4 percent, while the remaining 80.6 percent is influenced by other variables not examined in this study. The conclusion of this study is that the Product Completeness variable affects the Consumer Purchasing Decision variable at the Mutiara Jaya Pekanbaru Retail Store. etc.